G575(P) Neonatal T cells acquire both pro-inflammatory and tolerant phenotypes in first three weeks of life. (25th October 2020) - Toldi, G; Wood, H; Powell, R; Ewer, A; Moss, P
Abstract : The neonatal immune system needs to rapidly adapt to environmental changes following delivery in order to fight pathogens and tolerate harmless antigens. The precise kinetics of these changes and the key cellular and soluble components of the immune system remain to be elucidated. We aimed to describe changes in the immune phenotype of neonates in the first 3 weeks of life following delivery. We collected cord blood samples from 19 healthy, term neonates delivered by elective Caesarean sections. A pre-delivery maternal peripheral blood sample was also obtained. The neonates were re-sampled for peripheral blood at 3 weeks of age. Mononuclear cells were isolated from these samples and were measured on 2 flow cytometry panels consisting of a total of 20 intracellular and cell surface markers. The proportion of IL-8-producing CD4 and CD8 cells was lower in maternal compared to neonatal samples. Intracellular IL-17 production of CD4 and CD8 cells increased by 3 weeks of age compared to cord blood. The proportion of Tregs (CD4+ CD25high FoxP3+) increased by 3 weeks compared to cord blood, but remained lower in comparison to maternal samples. The proportion and cytotoxic activity (CD107a+) of CD8 cells, as well as the proportion of IFN-gamma-producing CD4 and CD8 cells were lower in neonatal compared to maternal samples. The proportion of HLA-DR+ and CD69+ T cells was also lower in neonatal compared to maternal samples. While neonatal T cells maintain an IL-8 phenotype during the first 3 weeks of life, they also acquire an IL-17 phenotype, possibly contributing to their ability to fight infection. On the other hand, the proportion of Tregs also increase by 3 weeks of age, playing an important role in establishing tolerance towards harmless environmental antigens.